Psychosocial factors associated with anemia among pregnant women attending a community health center - Epi Putriani Zebua; Ariska Fauzianty; Juliyanti Pasaribu; Azrina Fetta Tanjung; Nova Isabella Mariance Br Napitupulu (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Anemia during pregnancy remains a major public health problem because it increases the risk of adverse maternal and fetal outcomes. Psychosocial factors, including husband's support, adherence to iron supplementation, self-efficacy, and maternal knowledge, may influence anemia prevention behaviors. Purpose: To analyze the association between psychosocial factors and the incidence of anemia among pregnant women in the Sentosa Baru Community Health Center working area. Method: A quantitative cross-sectional study was conducted among 64 pregnant women selected using total sampling. Data on psychosocial factors were collected using validated questionnaires, while hemoglobin levels were obtained from medical records or maternal health books. Data were analyzed using Chi-square tests and multiple logistic regression. Results: Of the 64 respondents, 46 (71.9%) experienced anemia. Bivariate analysis demonstrated significant associations between husband's support (p=0.002), iron supplementation adherence (p=0.004), self-efficacy (p=0.001), knowledge (p=0.001), and anemia incidence. Multiple logistic regression identified husband's support (adjusted OR=8.273; 95% CI: 2.037–23.814; p<0.05), iron supplementation adherence (adjusted OR=5.938; 95% CI: 1.784–19.759; p<0.05), self-efficacy (adjusted OR=0.087; 95% CI: 0.020–0.389; p<0.05), and maternal knowledge (adjusted OR=8.273; 95% CI: 2.408–28.416; p<0.05) as significant factors associated with anemia. Conclusion: Psychosocial factors are significantly associated with anemia among pregnant women. Strengthening family support, improving adherence to iron supplementation, enhancing self-efficacy, and increasing maternal knowledge should be integrated into anemia prevention programs during pregnancy.